Pengaruh BOPO, FDR dan Faktor Eksternal terhadap Profitabilitas Bank Muamalat pada Periode 2014-2022 - Risya Tri Annisa (ITB AAS INDONESIA Surakarta, 2023)
This research analyzes the relationship of financial ratios and external factors that affect profitability in Muamalat, TBK Bank, This research uses a time series that uses the 2014-2022 data..The result is BOPO, FDR, BI Rate and Inflation affect ROA in simultaneously. But in Partial results only BOPO and FDR affected ROA. r-square having results 0.965103, where this proved that BOPO, FDR, BI Rate and Inflation have 96,5% contribution to ROA simultaneously.